Pengembangan Literasi Keagamaan Dalam Pembelajaran Pendidikan Agama Islam di SMA Daarul Abroor - Fahri, Ahmad; Meitama, Ratu Pinkan; Azhari, Ainul; Halimah, Nur (Abdimas Mandalika, 2026)
Abstract:  This Community Service Program (PKM) aims to strengthen religious literacy in Islamic Religious Education (PAI) learning through the Participatory Learning and Action (PLA) approach. The program was implemented at SMA Daarul Abroor Lebak Wangi, involving PAI teachers, students, the PKM team, and PPKT (Integrated Teaching Professional Practice) student teachers. The implementation method consisted of several stages: needs identification through classroom observation and pre-test, participatory planning through a participatory planning workshop, implementation of a literacy-based learning model (reading–understanding–reflecting–applying), and participatory process and outcome evaluation. The needs assessment revealed that PAI learning was still predominantly teacher-centered and had not fully integrated contextual religious literacy. The implementation of the literacy-based learning model led to a more dialogical and reflective classroom dynamic, as indicated by increased student participation and improved text-based argumentation grounded in Islamic sources. The pre-test and post-test results demonstrated an improvement in students’ average scores from 68.4 to 82.7. Participatory evaluation also revealed a shift in teachers’ perceptions of religious literacy—not merely as reading religious texts, but as a process of understanding, analyzing, and internalizing Islamic values in daily life. Therefore, the PLA approach proved effective in enhancing the quality of religious literacy-based PAI learning and strengthening teachers’ pedagogical capacity.Abstrak: Kegiatan Pengabdian kepada Masyarakat (PKM) ini bertujuan untuk memperkuat literasi keagamaan dalam pembelajaran Pendidikan Agama Islam (PAI) melalui pendekatan Participatory Learning and Action (PLA). Program dilaksanakan di SMA Daarul Abroor Lebak Wangi dengan melibatkan guru PAI, siswa, tim PKM, serta mahasiswa PPKT (Praktik Profesi Keguruan Terpadu). Metode pelaksanaan mencakup tahapan identifikasi kebutuhan melalui observasi dan pre-test, perencanaan partisipatif melalui workshop participatory planning, implementasi pembelajaran berbasis model literasi (reading–understanding–reflecting–applying), serta evaluasi proses dan hasil secara partisipatif. Hasil identifikasi menunjukkan bahwa pembelajaran PAI masih cenderung berpusat pada guru dan belum mengintegrasikan literasi keagamaan secara kontekstual. Implementasi model pembelajaran menunjukkan perubahan dinamika kelas yang lebih dialogis dan reflektif, ditandai dengan meningkatnya partisipasi siswa dan kualitas argumentasi berbasis dalil. Hasil pre-test dan post-test menunjukkan adanya peningkatan rata-rata nilai siswa dari 68,4 menjadi 82,7. Evaluasi partisipatif juga mengungkap perubahan persepsi guru terhadap literasi keagamaan sebagai proses memahami, menganalisis, dan menginternalisasi nilai ajaran Islam dalam kehidupan. Dengan demikian, pendekatan PLA efektif dalam meningkatkan kualitas pembelajaran PAI berbasis literasi keagamaan serta memperkuat kapasitas pedagogis guru.